Community Based Tourism and Poverty Alleviation: Evaluating the Success of PakuanVIT's Integrated Approach - Harjanto, Vrisco; Kurniawati, Aprilina; Sulhana El Fiesha Balqis, Putri (Green Publisher, 2024)
This paper emphasizes the significant contribution of the tourism sector in poverty alleviation through community empowerment within the Village Tourism program. The aim of this study is to elaborate on a program designed to be more applicable and to deliver tangible impacts. The research method used in this study is participatory observation, involving key community figures in Pakuan village as informants. The Village Tourism program, named PakuanVIT, has demonstrated social, economic, environmental, and well-being impacts through the social innovation carried out by the CSR program of PT Pertamina Patra Niaga Integrated Terminal Ampenan. The integration of four aspects of community empowerment within PakuanVIT is key to the program's sustainability, which is expected to significantly reduce poverty levels.